Financial systems - importance, differences and convergence - Reinhard H. Schmidt; Aneta Hryckiewicz (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2006)
This paper provides an overview of conceptual issues and recent research findings concerning the structure and the role of financial systems and an introduction into the new research area of comparative financial systems. The authors start by pointing out the importance of financial systems in general and then sketch different ways of describing and analysing national financial systems. They advocate using what they call a “systemic approach”. This approach focuses on the fit between the various elements that constitute any financial system as a major determinant of how well a given financial system performs its functions. In its second part the paper discusses recent research concerning the relationships between financial sector development and general economic growth and development. The third part is dedicated to comparative financial systems. It first analyses the similarities and, more importantly, the differences of the financial systems of major industrialised countries and points out that these differences seem to remain in existence in spite of the current wave of liberalisation, deregulation and globalisation. This leads to the concluding discussion of what the systemic approach suggests with respect to the question of whether the financial systems of different countries are likely to converge to a common structure.
urn:nbn:de:hebis:30-70340
Keywords: G32; G34; G38; 330; Financial sector; financial system; growth and development; convergence